Photographic Study of Lip Anthropometric Pattern Development in the Fars Family in Mashhad - Mehrnaz Abrishami; Naser Mahdavi Shahri; Jina Khayat zadeh (Negah Institute for Scientific Communication, 2014)
Introduction: Anthropometry (morphometry of the human) is measurement of linear and angular dimensions of the human body. Since the anthropometric parameters which are based on age, sex, geographical location and ethnic characteristics of the human species are different, therefore, anthropometric studies of population by age and sex should be done separately. Methods: In this study, anthropometric measurements lips and different patterns of lip line were studied in 133 males (4-40 years) with Persian ethnic who were living in Mashhad. These persons had no inflammation, herpes, malformations such as cleft lip, and surgery history in lib and jaw. Lip full-face photos were taken using a digital camera (Nikon, 12.3 Mega Pixels). Anthropometric measurements of mouth width (ch-ch) width of philtrum (cph-cph) height of the total lip ((ls-li) the entire lip area (total area) were measured on computer by MIP software. Data were evaluated statistically using SPSS, polynomial regression and ANOVA models (P<0.001). Results: There was a significant correlation between age and parameters of the mouth width, lips height to nose and total area of the lip. Conclussion: Considering significant relationship between the quantities investigated and age, we can use anthropometric data of lips in many fields including medical, criminal, etc. By comparing this study with other studies, it can be concluded that there is the most similarity in the size of lip of Persian men in Mashhad with men living in India. It is hoped that in the similar future studies, extensive statistical societies be prepared in each races of Turks, Baluchis, Kurds in order to complete anthropometric database of lip in Iranian Persian ethnics.